2021
DOI: 10.1111/adb.13089
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine hydrolase blocks cocaine‐induced dopamine transporter trafficking to the plasma membrane

Abstract: Cocaine blocks dopamine uptake via dopamine transporter (DAT) on plasma membrane of neuron cells and, as a result, produces the high and induces DAT trafficking to plasma membrane which contributes to the drug seeking or craving. In this study, we first examined the dose dependence of cocaine-induced DAT trafficking and hyperactivity in rats, demonstrating that cocaine at an intraperitoneal dose of 10 mg/kg or higher led to redistribution of most DAT to the plasma membrane while inducing significant hyperactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(45 citation statements)
references
References 51 publications
(111 reference statements)
0
44
0
Order By: Relevance
“…Our previous study 11 reported that in normal rat brain, striatal DAT mainly existed in the intracellular fraction, with only a very small fraction (~5.7%) existed in the plasma membrane in rats. Notably, our finding of only ~5.7% of DAT in the plasma membrane surface in rat brain is far less than the previously reported surface DAT fraction in cultured PC12‐hDAT cells (~25–40%), 38–40 ) but is close to the synaptosomal surface faction (~7%) of DAT in rats reported by Johnson et al 41 Cocaine at an i.p.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Our previous study 11 reported that in normal rat brain, striatal DAT mainly existed in the intracellular fraction, with only a very small fraction (~5.7%) existed in the plasma membrane in rats. Notably, our finding of only ~5.7% of DAT in the plasma membrane surface in rat brain is far less than the previously reported surface DAT fraction in cultured PC12‐hDAT cells (~25–40%), 38–40 ) but is close to the synaptosomal surface faction (~7%) of DAT in rats reported by Johnson et al 41 Cocaine at an i.p.…”
Section: Resultsmentioning
confidence: 91%
“…We previously demonstrated 11 that cocaine at an intraperitoneal dose of 10 mg/kg or higher induced trafficking of most DAT to the plasma membrane (with only <5% remained in the intracellular) at 24 h after cocaine injection in rats. In current study, we aimed to reveal how long it could take for the dopaminergic system recovering to its normal status (in terms of intracellular and plasma membrane fractions of DAT) in rats.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations